Membangun Kinerja UMKM Melalui Inovasi Keuangan - Thohary, Ruby; Guarto, Muji; Verawaty, Verawaty (Catholic University Musi Charitas, 2022)
The purpose of this study is to explain the effect of financial innovation on the performance of MSMEs in the city of Palembang. This type of research is a quantitative study with an analysis unit of MSMEs in Palembang City, where the number of samples in this study were 100 respondents from a population of 20,648 MSME actors in the culinary sector in Palembang City. Sampling was carried out using the Probability Sampling method, with the Simple Random Sampling Technique. The analysis technique in this research is descriptive statistics and inferential statistics with Structural Equation Modeling (SEM) approach using lisrel software. The results of this study indicate that financial innovation has a significant positive effect on the performance of MSMEs. This means that the stronger the financial innovation carried out by MSME actors, the more they will improve and build a good and effective performance.